2007
DOI: 10.2353/ajpath.2007.060903
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Protein Acidic and Rich in Cysteine (SPARC) Inhibits Integrin-Mediated Adhesion and Growth Factor-Dependent Survival Signaling in Ovarian Cancer

Abstract: The matricellular glycoprotein SPARC (secreted protein acidic and rich in cysteine) has been accorded major roles in regulation of cell adhesion and proliferation, as well as tumorigenesis and metastasis. We have recently reported that in addition to its potent antiproliferative and proapoptotic functions, SPARC also abrogates ovarian carcinoma cell adhesion, a key step in peritoneal implantation. However, the underlying molecular mechanism through which SPARC ameliorates peritoneal ovarian carcinomatosis seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 38 publications
5
97
0
Order By: Relevance
“…6). SPARC can be secreted to regulate local growth factor, ECM, and matrix metalloproteinase (MMP) activity, to modulate cell morphology and migration responses, angiogenesis, and cell proliferation and survival (Rempel et al, 2001;Francki et al, 2004;Barker et al, 2005a;Yan et al, 2005;Said et al, 2007a). In vitro, SPARC acts on many cell types as a deadhesive factor that induces cell rounding and inhibits cell migration (Sage et al, 1989b;Bradshaw and Sage, 2001), including on neuronal and glial cell lines (Ikemoto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6). SPARC can be secreted to regulate local growth factor, ECM, and matrix metalloproteinase (MMP) activity, to modulate cell morphology and migration responses, angiogenesis, and cell proliferation and survival (Rempel et al, 2001;Francki et al, 2004;Barker et al, 2005a;Yan et al, 2005;Said et al, 2007a). In vitro, SPARC acts on many cell types as a deadhesive factor that induces cell rounding and inhibits cell migration (Sage et al, 1989b;Bradshaw and Sage, 2001), including on neuronal and glial cell lines (Ikemoto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, SPARC is thought to act in vivo as a contextual regulator of cellular adhesion strength (Greenwood and Murphy-Ullrich, 1998), and is required for fibroblast migration during dermal wound healing (Basu et al, 2001), leukocyte infiltration after immune challenge (Kelly et al, 2007;Rempel et al, 2007), and tumor invasiveness (Rempel et al, 2001;Framson and Sage, 2004). SPARC modulates cell morphology, migration, and survival via signaling pathways that include integrin-linked kinase (ILK), focal adhesion kinase (FAK), mitogen-associated protein kinase (MAPK), and AKT/protein kinase B (Shi et al, 2004(Shi et al, , 2007Barker et al, 2005a;Said et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports highlight the role of this molecule as a positive or negative modulator in the pathogenesis of different malignancies (18)(19)(20)(21)(22)(23)(24). We and others have shown that SPARC functions as a tumor suppressor in ovarian cancer (25)(26)(27)(28). As a tumor suppressor, effect of SPARC in different cancers was attributed not only to its counteradhesive, antiproliferative functions but also to its role in modulating angiogenesis as well as regulation of the production, assembly, and organization of the structural extracellular matrix proteins including type I collagen and fibronectin (23,25,(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%